2017
DOI: 10.1159/000478668
|View full text |Cite
|
Sign up to set email alerts
|

Silver Diamine Fluoride Has Efficacy in Controlling Caries Progression in Primary Teeth: A Systematic Review and Meta-Analysis

Abstract: A systematic review was performed to evaluate the efficacy of silver diamine fluoride (SDF) in controlling caries progression in children when compared with active treatments or placebos. A search for randomized clinical trials that evaluate the effectiveness of SDF for caries control in children compared to active treatments or placebos with follow-ups longer than 6 months was performed in PubMed, Scopus, Web of Science, LILACS, BBO, Cochrane Library, and grey literature. The risk of bias tool from the Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
186
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(214 citation statements)
references
References 41 publications
11
186
0
17
Order By: Relevance
“…These 4 studies of permanent teeth have not been combined in a metaanalysis because they reported outcomes using different measures (number of teeth with new caries lesions or active lesions, in all surfaces vs only pit and fissure, and provide the data in different units of measurement [means and standard deviation vs number of events]). 51 No solid conclusions can be reached with such a small number of studies on permanent teeth in children.…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 98%
See 3 more Smart Citations
“…These 4 studies of permanent teeth have not been combined in a metaanalysis because they reported outcomes using different measures (number of teeth with new caries lesions or active lesions, in all surfaces vs only pit and fissure, and provide the data in different units of measurement [means and standard deviation vs number of events]). 51 No solid conclusions can be reached with such a small number of studies on permanent teeth in children.…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 98%
“…Based on the Gao 2016 metaanalysis, 18 the proportion of caries arrest on primary teeth treated with different application protocols (1 application, annual, and biannual), and followed from 6 to 30 months, was 81% (95% confidence interval, 68%–89% p <.001). Chibinski and colleagues (2017) 51 reported that the caries arrest at 12 months promoted by SDF was 66% higher (41%–91%) than by other active material, but it was 154% higher (67%–85%) than by no treatment. Chibinski and associated 51 also reported a risk ratio of 1.66 (95% confidence interval, 1.41–1.96) when comparing SDF with active treatments, and a risk ratio of 2.54 (95% confidence interval, 1.67–3.85) when comparing SDF with no treatment.…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
See 2 more Smart Citations
“…The use of SDF has recently gained interest due to its easy application and is a promising strategy that can be widely used in several populations, including those for whom restorative treatment is not possible. Moreover, previous studies have proved the efficacy of this material in the prevention and control of coronary caries progression, both in primary and in permanent teeth, and root caries lesions in permanent teeth . Thus, SDF usage could potentially increase access to health care and improve oral health, ultimately reducing the need for urgent care …”
Section: Introductionmentioning
confidence: 98%